The Private Label (Brand):Retailers' Value Proposition and Strategic Tool of Differentiation - Patil, Pravin Pandurand; Vedak, Vidyadhar (Indian Journal of Marketing, 2011)
The paper deals with retailer's private label (brand). Private Label is retailer's value proposition for customer i.e. good value for money. The study covers growth and global scenario of private labels, in developed countries. The primary focus of the study is to understand the awareness, preference of consumers towards private labels in India. The Study highlights the factors that impact merchandise choice while making buying decisions. A Private Label is a retailers' strategic tool for differentiation. Their own label is nurtured over the years by organized retailers. Branding, packaging, pricing and overall positioning of private labels is a challenge for retailers. Retailers negotiate on supply terms as well as on margin aspects with national brand manufacturers. It is based on retailer's category wise private label basket and visibility in the market. Indian consumers prefer national brands over private labels due to quality and trust worthiness factor. The paper covers private label strategic objectives, benefits and challenges faced by retailers.